Risk of Somatic Symptom Disorder in Social Media Users Exposed to Information COVID-19 - Isti Anindya; Alfred Renatho Tomhinsa (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2021)
Background: At the end of December 2019, the world received bad news regarding a new outbreak that emerged due to a viral infection. The disease that arises due to this viral infection is named COVID 19 (Coronavirus Disease 19). The easiest access to news to get information about COVID19 is social media. Unwise use of social media can increase the risk of psychological disorders, one of which is somatic symptoms. Objectives: The purpose of this study was to look at the risk of somatic symptoms in social media users who were exposed to information about COVID-19 during the pandemic. Methods: The research method used a cross-sectional approach with an online survey method (391 respondents). The research tool used was a modification of the Somatic Symptom Inventory-24 item instrument and social media activity instruments. Results: The results of the study found that 74.5% of respondents were at risk of experiencing somatic symptoms in the moderate to low category (score ≤ 48) for users with low social media activity and 25.5% of respondents on high activity. A statistical relationship was found between somatic symptoms and social media activity with a p-value of 0.000 which means ≤ 0.005 (chi-square). Social media users with high and low activity had the same risk of experiencing somatic symptoms (OR = 1,061). Conclusion: The activities of accessing COVID-19 information through social media need to be limited to prevent the emergence of psychological disorders.